Analytical Accuracy of a Continuous Glucose Monitor in Adult Diabetic KetoacidosisTake-Home Points - Nathan L. Haas, MD; Lynn Ang, MD; Nazanene H. Esfandiari, MD; Ahsan M. Khan, MBBS; James A. Cranford, PhD; Ashley Cohen, MD; Jordan Sell, MD; Mostafa Abdel-Hamid, MD; Kevin E. Romanchik, BSN, RN; Frederick K. Korley, MD, PhD (CHEST Critical Care)
Background: Management of diabetic ketoacidosis (DKA) requires frequent point-of-care blood glucose (POCBG) measurements, often necessitating ICU admission and incurring substantial costs. Replacing hourly POCBG measurements with continuous glucose monitoring (CGM) could optimize DKA management by minimizing resource use and detecting hypoglycemic events earlier. However, the accuracy of CGM in DKA is not well established. Research Question: What is the clinical and analytical accuracy of CGM in adults with DKA? Study Design and Methods: This was a prospective observational study at a single academic medical center emergency department. Adults older than 18 years with DKA were included. Glucose was measured every 5 minutes via Dexcom G6 CGM and compared with hourly POCBG measurements until resolution of DKA. The primary outcome was proportion of paired CGM and POCBG values in Clarke error grid zones A and B. Additional outcomes included level of agreement via Bland-Altman plot, mean absolute relative difference, and time of first detection of glucose < 150 mg/dL. Results: Twenty adult patients with DKA were studied. Mean age was 42 years, 60% were female, 70% had type I diabetes, and mean presenting pH was 7.17. Three hundred thirty-four paired measurements from CGM and POCBG measurements were analyzed. Clarke error grid analysis revealed 97.0% of readings to be within zones A and B. Bland-Altman analysis showed the average difference between CGM and POCBG measurement was 26.0 mg/dL (95% limits of agreement, –70.7 to 122.6). Mean absolute relative difference was 28.6% (95% CI, 26.5%-30.6%). The first incidence of glucose < 150 mg/dL (n = 14) was detected 28.9 minutes earlier by CGM than POCBG measurements. Interpretation: In this study, CGM provided accurate measurements of blood glucose and identified missed opportunities for earlier intervention in adults with DKA. Future interventional trials can assess the impact of CGM-guided DKA management on patient outcomes, patient experience, and resource use.